Pesticides and environmental suffering: perspectives from the social sciences - Mora Solano, Sindy (2014)
In this paper I expose some issues that were discussed in the Jornadas de Reflexión de Ciencias Sociales. In this activity were exposed some results from a research about the study case of former banana workers who have been affected by the use of Nemagon (DBCP). The article suggests some analytical perspectives to recognize the contributions from social science to understand the use and consequences of pesticides